Pengaruh Kualitas Pelayanan Dan Inovasi Layanan Digital PLN Mobile Terhadap Kepuasan Pelanggan PT PLN (Persero) Unit Pelaksana Pelayanan Pelanggan (UP3) Mamuju - Yusuf, Basri; Arif, Muhammad Ridwan; Rukaiyah, St (STIM-LPI Makassar, 2025)
This study aims to analyze the influence of service quality and digital service innovation through the PLN Mobile application on customer satisfaction at PT PLN (Persero) Customer Service Implementation Unit (UP3) Mamuju. The research employs a quantitative method with a survey design, involving 100 respondents selected through the Simple Random Sampling technique. Service quality is measured using the SERVQUAL model, encompassing five dimensions: Tangibility, Reliability, Responsiveness, Assurance, and Empathy. Digital service innovation is assessed through three dimensions: Perceived Usefulness, Perceived Ease of Use, and User Experience. Data were collected via an online questionnaire using a Likert scale and analyzed with multiple linear regression. The results indicate that service quality (p-value < 0.001) and digital service innovation (p-value < 0.001) individually and simultaneously have a significant impact on customer satisfaction, with a coefficient of determination (R²) of 87.3%. The dimensions of Reliability and Empathy from service quality, along with Perceived Ease of Use from digital service innovation, are the dominant factors influencing customer satisfaction. The study recommends enhancing Reliability and Empathy by improving electricity supply reliability and customer care, as well as optimizing the PLN Mobile application to enhance ease of use, particularly for customers with limited digital literacy.